Maqasid Al-Shari’ah is a Divine Shield of Islamic Policy - Bhat, Ali Muhammad (Journal of Islamic Thought and Philosophy, 2023)
Shari’ah is the divine law for human beings to regulate their lives according to the will of God. In academia, it became a central focus for a large number of Muslim and non-Muslim scholars. Some considered it revealed law while others considered it a Juristic extraction of law known worldwide as jurisprudence. But it is obvious it is divine in nature as elaborated by Muslim scholarship as per need and requirement for human welfare. In the contemporary era under the influence of secular teachings, the Euro-centric scholarship cogitates it as a private affair but relevant to some issues of Muslim life called personal law affairs and rituals but, Muslim scholarship considered standardized law related to all affairs of life from polity to justice so as to achieve nearness of God (taqwa). It is noteworthy that, though Ghazali codified Maqasid al-Shari’ah within five objectives, other scholars included other necessary aspects that govern all affairs of human life, so that no one will be ill-treated. They uphold that it is a human welfare methodology that necessarily, safeguards human interests at local and international levels and makes it incumbent to regulate Muslim life through inclusive and exclusive methods on a priority basis.